Vulnerability to failure of cable-stayed bridges for beyond-design basis wind events. (September 2018) - Ovett, Maximillian; Chorzepa, Mi G.; Durham, Stephan; Christian, Jason; Davis, Benjamin
Abstract: This paper develops a vulnerability assessment framework for cable-stayed bridges based on critical elements identified through a failure analysis. The framework refers to a simple and effective model developed to assess the vulnerability of a bridge failure due to beyond design-basis wind loads. The proposed framework differs from the probability-based approach in that it uses a cable-stayed bridge in operation, not a prototype bridge for fragility assessment, to identify critical elements vulnerable for a bridge failure. Furthermore, this study provides a detailed procedure to calculate the wind loads that account for varying wind speeds. The vulnerability index is defined as the demand-to-capacity ratio determined at threshold wind speeds. By assessing a cable-stayed bridge located in southeastern Georgia in the U.S., it is demonstrated how the proposed framework and analysis model can be successfully used to verify the results, identify critical elements associated with bridge failures for beyond design basis wind speeds, and assess the vulnerability. It is also concluded that a sensitivity analysis of significant variables such as aerodynamic pressure coefficients and dynamic load factor identified through this study is noteworthy, in order to accurately define analytical sensitivity and establish a practical limit on wind speeds for determining if a bridge closure is necessary thorough a vulnerability assessment study.